Identification of Methicillin-Resistant Staphylococcus Aureus From Methicillin-Sensitive Staphylococcus Aureus and Molecular Characterization in Quanzhou, China - Bai, Zhimin; Chen, Min; Lin, Qiaofa; Ye, Ying; Fan, Hongmei; Wen, Kaizhen; Zeng, Jianxing; Huang, Donghong; Mo, Wenfei; Lei, Ying; Liao, Zhijun (Frontiers in Cell and Developmental Biology, 2021)
To distinguish MRSA from MSSA in sequence level and test susceptibility to antibiotic of S. aureus isolated from Quanzhou hospitals and investigate the MRSA distribution of PVL , MLST, SCCmec and spa typing, to define virulence factor, molecular characteristics and antibiotic resistance profiles. MRSA (positive) and MSSA (negative) sequences were used to extract feature vectors of 188D, n-gram and 400D. Weka was applied to classify them. PVL gene of 65 MRSA isolates was detected by simple PCR and then observed by agarose gel electrophoresis. The spa was amplified by simple PCR, and the target gene fragments were sequenced to obtain multiple sets of 24 bp repeats. SCCmec typing was performed using multiplex PCR. Sequence alignment was performed using the MLST website to generate sequence clones. The eBRUST was used to generate cloned complexes (CC) and analyze the correlation between various types.The results show that the highest correctly classified rates from Weka were 91.94%, 70.16% and 62.90% for 188D, n-gram and 400D, respectively. Antimicrobial susceptibility test of the 81 S. aureus: Penicillin-resistant rate was 100%. Among the 65 MRSA clinical isolates, the positive rate of PVL was 47.7% (31/65). Seventeen distinct sequence types (STs) were identified and the most prevalent was ST59, next was ST239. 21 spa types were identified, spa t437 was the most predominant type. MRSA major clone types of molecular typing were CC59-ST59-spa t437-IV, CC59- ST59-spa t437-Ⅲ, CC8-ST239-spa t030-III/IV, CC5-ST5-spa t062-IV, respectively. 188D feature vectors can distinguish MRSA from MSSA successfully. In Quanzhou, No S.aureus was resistant to vancomycin, linezolid and teicoplanin. The resistance rate of the MRSA isolates to clindamycin, erythromycin and tetracycline was higher than that of the MSSAs. MRSA multiple resistance rate was very serious for suggesting a high pathogenic risk of MRSA infection. CC59-ST59-spa t437-IV was the main clone type in Quanzhou, which is rare in other parts of mainland China.